IDNLearn.com is the place where your questions are met with thoughtful and precise answers. Join our interactive community and get comprehensive, reliable answers to all your questions.

Which is equivalent to [tex][tex]$16^{\frac{3}{4} x}$[/tex][/tex]?

A. [tex]\sqrt[4]{16}^{3 x}[/tex]

B. [tex]\sqrt[4 x]{16}[/tex]

C. [tex]\sqrt[3]{16}^{4 x}[/tex]

D. [tex]\sqrt[3 x]{16}[/tex]


Sagot :

To find an expression equivalent to [tex]\( 16^{\frac{3}{4} x} \)[/tex], let's compare each option to the given expression. We will simplify each option and compare it to the original expression.

### Given Expression:
[tex]\[ 16^{\frac{3}{4} x} \][/tex]

#### Step 1: Simplify the Given Expression
First, express [tex]\( 16 \)[/tex] as a power of 2:
[tex]\[ 16 = 2^4 \][/tex]

Then, substitute this back into the expression:
[tex]\[ 16^{\frac{3}{4} x} = (2^4)^{\frac{3}{4} x} \][/tex]

Using the power rule [tex]\((a^m)^n = a^{m \cdot n}\)[/tex]:
[tex]\[ (2^4)^{\frac{3}{4} x} = 2^{4 \cdot \frac{3}{4} x} = 2^{3x} \][/tex]

So, the given expression simplifies to:
[tex]\[ 2^{3x} \][/tex]

### Now, let's analyze each option:

#### Option 1: [tex]\(\sqrt[4]{16}^{3 x}\)[/tex]

Rewrite [tex]\(\sqrt[4]{16}\)[/tex] as [tex]\(16^{1/4}\)[/tex]:
[tex]\[ \sqrt[4]{16}^{3 x} = (16^{1/4})^{3 x} \][/tex]

Substitute [tex]\(16 = 2^4\)[/tex]:
[tex]\[ (2^4)^{1/4} = 2^{4 \cdot 1/4} = 2^1 = 2 \][/tex]

Thus:
[tex]\[ (2)^{3 x} = 2^{3 x} \][/tex]

This expression is [tex]\(2^{3x}\)[/tex], which is the same as our simplified given expression. Hence, Option 1 is equivalent.

#### Option 2: [tex]\(\sqrt[4x]{16}\)[/tex]

Rewrite [tex]\(\sqrt[4x]{16}\)[/tex] as [tex]\(16^{1/(4x)}\)[/tex]:
[tex]\[ 16^{1/(4x)} \][/tex]

Substitute [tex]\(16 = 2^4\)[/tex]:
[tex]\[ (2^4)^{1/(4x)} = 2^{4 \cdot (1/(4x))} = 2^{1/x} \][/tex]

This expression is [tex]\(2^{1/x}\)[/tex], which is not the same as our simplified given expression. Hence, Option 2 is not equivalent.

#### Option 3: [tex]\(\sqrt[3]{16}^{4 x}\)[/tex]

Rewrite [tex]\(\sqrt[3]{16}\)[/tex] as [tex]\(16^{1/3}\)[/tex]:
[tex]\[ \sqrt[3]{16}^{4 x} = (16^{1/3})^{4 x} \][/tex]

Substitute [tex]\(16 = 2^4\)[/tex]:
[tex]\[ (2^4)^{1/3} = 2^{4 \cdot 1/3} = 2^{4/3} \][/tex]

Thus:
[tex]\[ (2^{4/3})^{4x} = 2^{(4/3) \cdot 4x} = 2^{16x/3} \][/tex]

This expression is [tex]\(2^{16x/3}\)[/tex], which is not the same as our simplified given expression. Hence, Option 3 is not equivalent.

#### Option 4: [tex]\(\sqrt[3x]{16}\)[/tex]

Rewrite [tex]\(\sqrt[3x]{16}\)[/tex] as [tex]\(16^{1/(3x)}\)[/tex]:
[tex]\[ 16^{1/(3x)} \][/tex]

Substitute [tex]\(16 = 2^4\)[/tex]:
[tex]\[ (2^4)^{1/(3x)} = 2^{4 \cdot (1/(3x))} = 2^{4/(3x)} \][/tex]

This expression is [tex]\(2^{4/(3x)}\)[/tex], which is not the same as our simplified given expression. Hence, Option 4 is not equivalent.

### Conclusion

The expression equivalent to [tex]\( 16^{\frac{3}{4} x} \)[/tex] is:
[tex]\[ \sqrt[4]{16}^{3x} \][/tex]

Thus, the correct answer is Option 1.
A…sorry im not typing out a long explanation, but it is A